Adaptation mechanisms of the immune reaction in rats under the influence of moderately low temperatures in combination with low frequency electromagnetic radiation - Litovchenko, Olena; Mishyna, Maryna; Zub , Kseniia (Problems of Cryobiology and Cryomedicine, 2020)
Abstract: The immune system maintains a balance between the body's vital functions and influence of exogenous factors. Immune mechanisms are activated by the innate and adaptive response that allows the body to adapt to new living conditions, characterized by the simultaneous action of various factors. An experimental research in rats (for 30 days) studied the effect of moderately low temperatures (2-6°C), or in combination with electromagnetic radiation (70 kHz, 600 V/m) on the immune system to establish the features of adaptive-immunological responses of an organism. It was found that the effect of moderately low temperatures compared with the combined influence of electromagnetic radiation had a more pronounced effect, which was manifested by activation of the complement system (increased C4 and C5), increased concentrations of immunoglobulins (IgM, IgG) and enhanced functional activity of spleen (increased lymphoid follicles and their reactive centers). However, under the combined influence of the factors, the changes were less pronounced and modified (decrease in C4 content), that indicated the development of negative cross-adaptation in the immune system of animals. Probl Cryobiol Cryomed 2020; 30(3): 256–269